Bioethics in the Public and Policy Spaces: Lessons from the Covid Years - Williams-Jones, Bryn; Abtroun, Sihem (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
The Covid-19 pandemic presented numerous ethical challenges, highlighting the critical role of bioethicists in public spaces and policymaking. Bioethicists acted as guardians against systemic injustices, critics of health policy decisions, and contributors to public debate. This text draws on our experiences as North American academic bioethicists to explore the different roles that bioethicists took during the pandemic, notably through media engagement, participation in policy-making, and in research and education. The pandemic underscored the importance of bioethics in the healthcare system and in research governance, the need for interdisciplinary collaboration, the importance of applying various ethics frameworks, and the need for effective communication to ensure practical ethical decision-making. It also demonstrated the distinct yet complementary roles of academic and professional bioethicists, with the former often serving as visible public critics, due to their academic liberty and independence, while the latter worked within their institutions to support clinicians and decision-makers, and to effect policy change. But these roles could also lead to tensions between academic and professional bioethicists, due to their different mandates, and both also experienced frustrations with the continued lack of understanding by some professionals and policy-makers regarding the pertinence and utility of bioethics to support ethically-informed decision-making. Ultimately, the pandemic was a pivotal time for bioethicists to influence public debate and policy, showcasing the field’s relevance and adaptability in addressing complex ethical issues.